Plant–herbivore interactions: Combined effect of groundwater level, root vole grazing, and sedge silicification. Issue 22 (30th October 2021) - Borowski, Zbigniew; Zub, Karol; Sulwiński, Marcin; Suska‐Malawska, Małgorzata; Konarzewski, Marek
Abstract: Accumulation of silica (Si) by plants can be driven by (1) herbivory pressure (and therefore plant–herbivore interactions), (2) geohydrological cycles, or (3) a combination of (1) and (2), with (1–3) possibly affecting Si concentration with a 1‐year delay. To identify the relative significance of (1–3), we analyzed the concentration of Si in fibrous tussock sedge ( Carex appropinquata ), the population density of the root vole ( Microtus oeconomus ), and the groundwater level, over 11 years. The largest influence of autumn Si concentration in leaves (Sileaf ) was on the level of the current‐year groundwater table, which was positive and accounted for 13.3% of its variance. The previous year's vole population density was weakly positively correlated with Sileaf, and it alone explained 9.5% of its variance. The only variable found to have a positive, significant effect on autumn Si concentration in rhizomes (Sirhiz ) was the current‐year spring water level, explaining as much as 60.9% of its variance. We conclude that the changes in Si concentration in fibrous tussock sedge are predominantly driven by hydrology, with vole population dynamics being secondary. Our results provide only partial support for the existence of plant–herbivore interactions, as we did not detect the significant effects of Si tussock concentration on the vole density dynamics. This was mainly due to the low level of silicification of sedges, which was insufficient to impinge herbivores. Future studies on plant–herbivore interactions should therefore aim at disentangling whether anti‐herbivore protection is dependent on threshold values of herbivore population dynamics. Furthermore, studies on Si accumulation should focus on the effect of water‐mediated Si availability. Abstract : To identify mechanisms of silica (Si) accumulation by plants, we analyzed Si concentration in fibrous tussock sedge ( Carex appropinquata ), the root vole ( Microtus oeconomus ) population density, and water table over 11 years. Changes in Si concentration in fibrous tussock sedge are predominantly driven by hydrology, whereas vole population dynamics are secondary. Our results only partially support the existence of plant–herbivore interactions, as we did not detect significant effects of Si tussock concentration on the vole population dynamics. This was mainly due to the low degree of silicification of sedges, which was insufficient to impinge herbivores.